Statistika : Senjata Rahasia Mahasiswa di Era Big Data - Harefa, Dorthea Elvita; Buulolo, Talabu Karyaman Tuyamaku (CV. SINAR HOWUHOWU, 2025)
The era of big data has transformed the landscape of various industries and disciplines, creating a demand for professionals capable of analyzing and interpreting data on a large scale. This article explores the crucial role of statistics as a fundamental skill for students in the big data era. Through a comprehensive literature review and case study analysis, this research demonstrates how mastery of statistics can provide a competitive advantage for students in an increasingly data-driven job market. Findings indicate that students with strong statistical skills have broader career opportunities and better abilities in data-driven decision making. This article also highlights the importance of integrating contextual and project-based statistics education in higher education curricula to prepare students for the challenges of the big data era.